The Oxford handbook of economic and institutional transparency - Forssbaeck, Jens, 1970-; Oxelheim, Lars (New York : Oxford University Press, 2014)
'Transparency' has become both a catch-word in public debate and also an important research topic. Comprised of authoritative yet accessible contributions, this handbook surveys existing economic research on transparency and provides an up-to-date account of its meaning and significance in economic policy, market integration and regulation, and corporate governance and disclosure.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on December 3, 2014).
Keywords: Economics -- Philosophy; Economics -- Moral and ethical aspects; Transparency in government